Thus spoke peptides: SARS-CoV-2 spike gene evolved in humans and then shortly in rats while the rest of its genome in horseshoe bats and then in treeshrews - Flegr, Jaroslav; Zahradník, Daniel; Zemková, Michaela (Communicative & integrative biology, 2022)
SARS-CoV-2 is suspected to be the product of a natural or artificial recombination of two viruses - one adapted to the horseshoe bat and the other, donor of the spike protein gene, adapted to an unknown species. Here we used a new method to search for the original host of the ancestor of the SARS-CoV-2 virus and for the donor of its gene for the spike protein, the molecule responsible for binding to and entering human cells. We computed immunological T-distances (the number of different peptides that are present in the viral proteins but absent in proteins of the host) between 11 species of coronaviruses and 38 representatives of the main mammal clades. Analyses of pentapeptides, the presumed principal targets of T-cell non-self recognition, showed the smallest T-distance of the spike protein of SARS-CoV-2 to humans, while the rest of SARS-CoV-2 proteome to the horseshoe bat. This suggests that the ancestor of SARS-CoV-2 was adapted to bats, but the spike gene donor was adapted to humans. Further analyses suggest that the ancestral coronavirus adapted to bats was shortly passaged in treeshrews, while the donor of the spike gene was shortly passaged in rats before the recombination event.